Perlaksanaan sistem pengurusan keselamatan dan kesihatan pekerjaan di makmal perubatan : faktor dorongan dan halangan utama - Anuar I.,; Zahedi F.,; Kadir A.,; Mokhtar A. B., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
Background : The implementation of Occupational Safety and Health Management System(OSHMS) requires a level of measurement. The effectiveness of OSHMS implementation was influenced by inhibiting and supporting factors. The objective of this study was to determine the inhibiting and supporting factors towards the implementation of OSHMS in medical laboratories. Methodology : The implementation of Occupational Safety and Health Management System(OSHMS) requires a level of measurement. The effectiveness of OSHMS implementation was influenced by inhibiting and supporting factors. The objective of this study was to determine the inhibiting and supporting factors towards the implementation of OSHMS in medical laboratories. Result : This study showed the level of compliance to the OSHMS MS1722 guideline among medical laboratories who are MS ISO 15189 accredited & have a higher scores in overall measurement indicators OSHMS compared to those do not have SAMM accreditation. Private medical laboratories services have higher scores in overall measurement indicators OSHMS, compared to government medical laboratories. However, there was no significant difference (p>0.05) between medical laboratories which have ISO 9000 quality management system certification, compared to level of compliance to the OSHMS MS 1722 guideline among medical laboratories. Therewas also no significant difference (p>0.05) between the laboratories who had been operating for more than 10 years compared to those with less than 10 years, towards implementing the OSHMS. Results showed that majority of medical laboratories management perceived that difficulty and complexities of OSH legislation are the most important factor that prevent them from implementing OSHMS in their organization. The most important supporting factor, that medical laboratories management perceived as the most important to comply to the OSHMS were their moral responsibilities towards the community. Conclusion : In conclusion, the study shows there were many inhibiting and supporting factors that contribute towards effective implementation of OSHMS elements in workplace.